Roads and Roadlessness: Driving Trucks in Siberia - Tatiana Argounova-Low (Journal of Ethnology and Folkloristics)
This article relates to the studies of roads and engages with the experience of driving in Sakha (Yakutiia), Siberia. The article intends to contribute to the broad corpus of literature on mobility and argues that an alternative perspective on roads and road-users from a geographical area beyond the West might better inform and add another dimension to our notions of roads and our movement along them. The article examines the fluid nature of roads in Siberia and the social significance the roads carry by focussing on truck-drivers and their perception and engagement with the so-called winter roads through their sensory experiences. The article analyses narratives of the truckers who frame their experiences of the road with close reference to time and money and where notions of agency of the road become prominent.